2023
DOI: 10.7759/cureus.36565
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Irritable Bowel Syndrome: A Review Article

Abstract: Irritable bowel syndrome (IBS) is a persistent set of symptoms that reduces one's goodness of life. The treatment of these people is usually focused on reducing the symptoms caused by the condition. This article examines the function of probiotics in alleviating symptoms in IBS patients. The goal of studying the impact of probiotics on IBS patients is to research the changes they cause to the gut microbiota, which may be beneficial in preventing and treating such diseases over time. This article also discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This revealed a reduction in abdominal pain, stool frequency, and distension. L. acidophilus will be able to act visceral sensitivity by increasing the opioid and cannabinoid receptors in the intestinal mucosa [ 23–25 ]. However, Hadjimbei et al demonstrated that the lactic ferments S. Thermophilus and Lactobacillus bulgaricus are types of probiotics that enhance the functioning of the intestines, reduce the intensity of infectious diarrhoea, have a positive impact on diarrhoea after antibiotic treatment, and improve the elimination of Helicobacter pylori by 5 to 15% [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This revealed a reduction in abdominal pain, stool frequency, and distension. L. acidophilus will be able to act visceral sensitivity by increasing the opioid and cannabinoid receptors in the intestinal mucosa [ 23–25 ]. However, Hadjimbei et al demonstrated that the lactic ferments S. Thermophilus and Lactobacillus bulgaricus are types of probiotics that enhance the functioning of the intestines, reduce the intensity of infectious diarrhoea, have a positive impact on diarrhoea after antibiotic treatment, and improve the elimination of Helicobacter pylori by 5 to 15% [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of these latter findings, a manipulation of the microbiota has been proposed decades ago as a useful tool in the treatment of IBS [8] and growing evidence supports the effect of probiotics, that is "live microorganisms which when administered in adequate amounts confer a health benefit on the host" (well-known even before the pioneering studies of Elia Metchnikoff at the beginning of the 20th century: see for example Deuteronomy 32:14 where fermented milk is cited as a beneficial food given by God to humanity) in this regard [9][10][11]. Moreover, research on probiotics has been recently enclosed in the 10-item list of top research priorities in IBS [12] and in fact controlled clinical trials, meta-analyses and reviews regarding the efficacy of probiotics in IBS abound in the literature [13][14][15][16][17]. These are truly powerful research tools, but their results do not always reflect what happens in the real world both because they are derived from a minority of the IBS population since the majority is cared for in primary care [18,19] and because their effects may not influence the prescribing attitudes of general practitioners [20].…”
Section: Preprintsmentioning
confidence: 99%
“…The mechanism of action of probiotic preparations is not fully understood. It is noted that it may inhibit the development of IBS in particular post-infectious IBS, as they exhibit anti-inflammatory, antimicrobial and antiviral effects [ 69 ]. It is likely that probiotics modify the body’s immune system response by modifying the response of dendritic cells and stimulating the production of antimicrobial proteins [ 69 , 70 ].…”
Section: Supplementationmentioning
confidence: 99%
“…It is noted that it may inhibit the development of IBS in particular post-infectious IBS, as they exhibit anti-inflammatory, antimicrobial and antiviral effects [ 69 ]. It is likely that probiotics modify the body’s immune system response by modifying the response of dendritic cells and stimulating the production of antimicrobial proteins [ 69 , 70 ]. Probiotics can relieve abdominal pain by increasing the expression of cannabinoid and opioid receptors [ 71 ].…”
Section: Supplementationmentioning
confidence: 99%
See 1 more Smart Citation